Wer sieht das, was wir nicht sehen? Überlegungen zum Subjekt der Ideologiekritik - Bandelin, Sebastian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
The critique of ideology has often been criticised because it seems to imply a problematic gap between the perspective of the critical sociologist and that of the actor. The following article tries to show that the conception of the critique of ideology developed by Marx in his writings on the critique of political economy can avoid this problem insofar as the conception can be reconstructed as an instrument to explain the practical contradictions with which the actors are confronted in capitalist societies. The way in which these practical contradictions are explained shows also that the structures which first seemed to be natural preconditions for the actors are in fact the product of their actions.